Pendidikan perdamaian dan teknologi: Strategi untuk memberdayakan Madrasah ramah anaka - Inayati, Isna Nurul; Irianto, Alif Dedy (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The phenomenon of bullying remains a serious challenge in Indonesia’s educational landscape. According to data from the Ministry of Women’s Empowerment and Child Protection, there were more than 12,000 reported cases of violence against children in educational settings, with approximately 28% occurring at the elementary school level. This condition highlights the urgent need for preventive and curative strategies grounded in values and educational technology. The anti-bullying program at MI IMAMI Kepanjen was developed to foster empathy, tolerance, and mutual respect among students. Its implementation includes teacher training, the formation of a prevention team, a digital campaign titled “Stop Bullying,” the creation of student-produced educational videos, and socialization activities involving parents. This study aims to analyze the effectiveness of the anti-bullying program in strengthening the implementation of the Child-Friendly Madrasah policy at MI IMAMI Kepanjen through the integration of peace education values and learning technology. The study employs a descriptive qualitative approach using the interactive analysis model by Miles and Huberman, which involves data reduction, data display, and conclusion drawing. Data were collected through participatory observation, in-depth interviews with the principal, teachers, students, and parents, as well as documentation of case reports and program activities. Source and technique triangulation were applied to ensure data validity. The findings reveal that the program successfully reduced bullying cases from six incidents in 2022 to two in 2024. Furthermore, teachers became more responsive, students were more courageous in reporting incidents, and parents participated more actively. The anti-bullying program proved effective not only in reducing acts of violence but also in strengthening Islamic character and fostering a safe, inclusive, and collaborative madrasah culture. This success was supported by policy reinforcement, teacher role modeling, parental involvement, and the use of technology as a medium for peace education.